2019
DOI: 10.3390/cryst9100509
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Differences and Similarities between Betaxolol Polymorphs

Abstract: Betaxolol belongs to the class of β1-adrenergic blocking agent. Several polymorphs of racemic betaxolol have been reported in the literature, but only one of them (BE_I) had the crystal structure determined from single-crystal X-ray diffraction. Here, we present a new crystalline phase of betaxolol (BE_IV). Its solid-state structure has been obtained from single-crystal X-ray diffraction data. The molecular and crystal arrangements of betaxolol in BE_IV have been further investigated by molecular modelling, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In the past, we have used X-ray diffraction (SCXRD, PXRD) thermoanalytical techniques (DSC, TGA, and HSM) and in-silico tools (e.g., modeling and data mining) to study the solid forms of APIs belonging to different classes (β-blockers, , NSAIDs) and in different forms (salts and metal complexes) and to correlate their structural and physicochemical properties. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, we have used X-ray diffraction (SCXRD, PXRD) thermoanalytical techniques (DSC, TGA, and HSM) and in-silico tools (e.g., modeling and data mining) to study the solid forms of APIs belonging to different classes (β-blockers, , NSAIDs) and in different forms (salts and metal complexes) and to correlate their structural and physicochemical properties. , …”
Section: Introductionmentioning
confidence: 99%
“…In the past, we have used X-ray diffraction (SCXRD, PXRD) thermoanalytical techniques (DSC, TGA, and HSM) and insilico tools (e.g., modeling and data mining) to study the solid forms of APIs belonging to different classes (β-blockers, 11,12 NSAIDs) and in different forms (salts 13−15 and metal complexes) 16 and to correlate their structural and physicochemical properties. 17,18 With this in mind, and as part of our ongoing structural study of (S)-ketoprofen (S-Ket, hereafter), 19−21 its DSs with (R)-(+)-and (S)-(−)-1-phenylethylamine (α-methylbenzylamine; R-PEA and S-PEA, hereafter, Scheme 1) were prepared and investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…showed that the metoprolol free base undergoes an anisotropic thermal expansion [8], while the polymorph I of the closely related β-blocker drug betaxolol [9] (see scheme 1) that gives rise to almost identical H-bond motifs ( (10), vide infra) [10] (see Figure 1) shows an isotropic thermal expansion. The same holds for polymorph IV of betaxolol [11], i.e., its crystal lattice isotropically expands/contracts on changing the temperature; however, in this case, the H-bond network is slightly different (alternating (10) and (8) patterns).…”
Section: Introductionmentioning
confidence: 68%
“…In particular, valuable information on the molecular and crystal structures of the corresponding crystalline solids have been extracted and correlated to their properties, e.g. , isotropic vs anisotropic thermal expansion, chiral recognition, phase stability/transformation, solvation/desolvation processes, and polymorphic behavior. …”
Section: Introductionmentioning
confidence: 99%